White spruce tree-ring-width data in Old Crow Flats, Yukon Territory, 2007-2008 - Nagwan, Lance; Porter, Trevor J.; Pisaric, Michael F.J. (Canadian Cryospheric Information Network, 2014)
A network of 23 white spruce sites was established in Old Crow Flats, and tree-ring samples were collected from each site using standard dendrochronological techniques. Cores were collected from living trees and cookies were cut from dead trees. Ring-width series were measured from all samples at the Carleton University Paleoecology Laboratory, and mean site chronologies were calculated for each site. Climate-growth relations of each site were assessed. Regional growth patterns were compared against other white spruce chronologies from across northwestern North America to determine the larger-scale importance of tree-ring growth in Old Crow Flats. For more details refer to Porter, Trevor J. and Michael F.J. Pisaric, 2011, Temperature-growth divergence in white spruce forests of Old Crow Flats, Yukon Territory, and adjacent regions of northwestern North America. Global Change Biology 17: 3418-3430, doi: 10.1111/j.1365-2486.2011.02507.x. : Purpose: The purpose of this research is to develop climatically sensitive tree ring records from the Old Crow Flats region. It is hoped that these records will extend the temporally short instrumental climate record from Old Crow which currently only covers the period 1951-2004. Such a short record makes it difficult to assess long-term climate trends and variability and accurately define baseline climatic conditions. By using proxy data sources such as tree ring growth records, we can extend the short instrumental climate record further back in time. It is anticipated that this research will produce climatically-sensitive tree ring chronologies extending over the past 2-3 centuries. : Summary: Not Applicable